CELEBRITY BOXING MATCHES IN RANS ENTERTAINMENT'S SUPERSTAR KNOCKOUT EVENT: BETWEEN SENSATION AND SUBSTANCE - Geofakta Razali; Widyastuti; Siska Armawati Sufa; Damayanti Masduki; R. Ayu Erni Jusnit (Adisam Publisher, 2024)
Celebrity boxing matches held by RANS Entertainment have two different opinions in response to it. On the one hand, he believes that this match has a lot of substance, namely raising the good name of Indonesian boxing and inspiring young people to channel their talents in positive ways and not commit criminal acts on the streets. However, on the other hand, they think this event is just a sensation because the match being held does not have good boxing standards, there are no professional boxers involved even though the event is an official event. Therefore, this research aims to describe whether the match only contains substance, vice versa, or contains both. This research is qualitative research with an explanatory approach. The data used in this research is secondary data that researchers obtained from websites, scientific articles, books and a number of other commonly used sources. These data were analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions.